Pembuatan Margarin dan Baking Shortening Berbasis Minyak Sawit Merah dan Aplikasinya dalam Produk Bakery - Hasrul Abdi Hasibuan; Ananta Akram; Pratiwi Putri; Bella Triana Rangkuti; Ennisa Cita Mentari (agriTECH, 2018)
Red palm oil (RPO) is a palm oil product that still retains carotene (pro vitamin A) in high contents. Diversification of RPO in food products should be developed to enhance consumers’ nutrition. This research was conducted to make margarine and baking shortening based on RPO and its application in baking products. The RPO used was neutralized crude palm oil (CPO) (RPO NPO) and from fresh fruit bunches (RPO FFB). Margarine was made into 2 types namely grade A (RPO 100%) and grade B (RPO: refined bleached deodorized palm oil (RBDPO) 50:50) and baking shortening also 2 types namely grade A (RPO: refined bleached deodorized palm stearin (RBDPS): refined bleached deodorized palm kernel oil (RBDPKO) 70:15:15) and grade B (RPO: RBBDPO (50:50): RBDPS : RBDPKO 70:15:15). Bakery products were made into 3 types of sweet bread, donuts and rolls cake. The margarine and baking shortening that obtained have high carotene, the peroxide value fulfills the standard of <10 mgeq/kg but high free fatty acid (FFA) about 0.1-0.3%, that is caused by RPO have high FFA. The sweet breads, donuts and rolls cake using RPO-based margarine and baking shortening have moisture content, fat content, FFA content, peroxide value and volume expansion (except donuts and rolls cake) similar to commercial products, but the carotene content was higher. Preference for color, aroma, texture and flavor of sweet breads, donuts and rolls cake using RPO : RBDPO (50:50) were quite high from RPO 100%, but lower compared to commercial products, relatively. Therefore, mixing of RPO and RBDPO can be an alternative in improving nutrition of bread products.